Model for predicting risk of developing drug-induced liver injury during remdesivir therapy: observational prospective open case-control study - Yu. V. Shevchuk; A. V. Kryukov; I. I. Temirbulatov; I. V. Sychev; K. B. Mirzaev; N. P. Denisenko; Sh. P. Abdullaev; S. N. Tuchkova; V. I. Vechorko; O. V. Averkov; D. A. Sychev (Фармация и фармакология (Пятигорск))
Remdesivir is a drug widely used for the etiotropic treatment of COVID-19. According to a number of studies, the incidence of adverse reactions during remdesivir therapy reaches 66%, with the most common is an increase in liver function tests.The aim of the work was to study the influence of clinical, demographic and pharmacogenetic factors on the development of drug-induced liver damage during remdesivir therapy in COVID-19 patients.Materials and methods. The study comprised 100 hospitalized patients treated with remdesivir. The patients were divided into two groups: group 1 (n=32) – remdesivir therapy, developed an increase in the level of liver transaminases; group 2 (control, n=68) – did not develop this adverse reaction. The patients in both groups underwent a pharmacogenetic study, and a retrospective analysis of medical records was performed. Based on the data obtained, the association of clinical, laboratory, pharmacological and pharmacogenetic parameters with the development of drug-induced liver damage during remdesivir therapy was studied.Results. In the group of patients with the development of drug-induced liver damage, people with a high body mass index were significantly more likely than in the control group (30.7±4.2 kg/m2 in group 1 vs. 27.3±5.5 kg/m2 in group 2, p=0.003), with a history of diabetes mellitus (odds ratio (OR)=2.647, 95% confidence interval (CI)=1.092–6.414, χ2=4.785, p=0.029), with higher levels of ferritin in the blood (724.03±432.27 and 553.19±358.48 mg/mol, respectively, p=0.040), receiving therapy with angiotensin-converting enzyme inhibitors (OR=5.440, 95% CI=2.160–13.699, χ2=14.027, p=0.000), statins (OR=3.148, 95% CI=1.307–7.581, χ2=6.795, p=0.009), and also being heterozygous for the polymorphic marker rs776746 of the CYP3A5 gene (OR=3.961, 95% CI=1.343–11.686, χ2=6.772, p=0.009).Conclusion. A high body mass index, a history of diabetes mellitus, high levels of ferritin in the blood, concomitant therapy with angiotensin-converting enzyme inhibitors and statins, as well as a carriage of the AG genotype for the polymorphic marker rs776746 of the CYP3A5 gene increase the likelihood of developing drug-induced liver damage during remdesivir therapy. In this regard, it is necessary to consider these factors when prescribing remdesivir therapy, conduct a more careful monitoring of clinical and laboratory indicators of liver damage, and develop personalized approaches to the treatment of COVID-19 patients.